2014
DOI: 10.1007/s00221-014-3885-1
|View full text |Cite
|
Sign up to set email alerts
|

Visual control of trunk translation and orientation during locomotion

Abstract: Previous studies have suggested distinct control of gait characteristics in the anterior–posterior (AP) and medial–lateral (ML) directions in response to visual input. Responses were larger to a ML visual stimulus, suggesting that vision plays a larger role in stabilizing gait in the ML direction. Here, we investigated responses of the trunk during locomotion to determine whether a similar direction dependence is observed. We hypothesized that translation of the trunk would show a similar ML dependence on visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…It might use sensory information from three modalities: the proprioceptive, visual and vestibular systems. Studies using visual perturbations of gait have shown compensatory trunk movements [ 60 ] and changes in foot placement [ 61 ] and, with continuous unpredictable visual perturbations, variability of both trunk movement and foot placement increased [ 62 ]. Vestibular stimulation [ 63 67 ] and proprioceptive stimulation through the vibration of trunk or neck muscles [ 68 ] lead to ample deviations of heading.…”
Section: Foot Placement In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…It might use sensory information from three modalities: the proprioceptive, visual and vestibular systems. Studies using visual perturbations of gait have shown compensatory trunk movements [ 60 ] and changes in foot placement [ 61 ] and, with continuous unpredictable visual perturbations, variability of both trunk movement and foot placement increased [ 62 ]. Vestibular stimulation [ 63 67 ] and proprioceptive stimulation through the vibration of trunk or neck muscles [ 68 ] lead to ample deviations of heading.…”
Section: Foot Placement In Humansmentioning
confidence: 99%
“…Empirical data indeed support that sensory weighting is different in walking than in standing. For example, vibration of the leg muscles had much more pronounced effects in standing than in walking [ 68 ], while effects of visual perturbations were larger in walking than in standing [ 60 ]. Moreover, the importance of visual perturbations in walking appears to be directionally specific with larger effects of ML perturbations than those of AP perturbations [ 60 , 61 ].…”
Section: Foot Placement In Humansmentioning
confidence: 99%
“…The current system setup has been described in detail in a previous aticle. 22 Trunk orientation was represented to the subject as the position of a moving cursor within a bull's-eye target on a 68.58 cm (27-inch) wide screen TV (ViewSonic VA2703, ViewSonic,Walnut, CA) mounted at standing eye level. Trunk orientation relative to vertical here is defined as AP and medial-lateral (ML) angular displacement of the segment defined by the naval marker to the midpoint of the acromion process markers.…”
Section: Walking Posture Control Assessmentmentioning
confidence: 99%
“…[13][14][15] We also investigated the control of balance during walking using visual feedback of the trunk while walking on a treadmill. 22 Our hypothesis is that these techniques are more sensitive to the subtle, transient effects of mild head impact with regard to the processing of vestibular information and postural stability under static and dynamic conditions.…”
mentioning
confidence: 99%
“…More recently, interest in the role of the visual system for balance control is expanding from standing to walking (Logan et al, 2010 ). While responses of the upper body seem to be somewhat similar between standing and walking at low frequencies, gains are higher during walking at high frequencies (Anson et al, 2014 ). This is no doubt due to the nature of the gait cycle, which has a strong modulating effect on balance responses in the lower body (Logan et al, 2014 ; Qiao et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%